2009
DOI: 10.1016/j.earlhumdev.2008.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of neurodevelopmental outcome for preterm infants with brain injury: MRI, medical and environmental factors

Abstract: This multi-center correlational prospective study examined early neonatal predictors of neurodevelopment in 59 premature infants (mean birth weight=1713.8±1242.5 g; mean gestational age=31.2±3.6 weeks) suspected to have sustained brain injury at birth. The mental and motor development of the infants selected from five university-affiliated hospitals was assessed at baseline (59 infants), 12 (55 infants), and 18 months (46 infants) using Bayley II scales. Factors correlating with Bayley II scores at 12 and 18 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
2
3

Year Published

2009
2009
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 47 publications
3
22
2
3
Order By: Relevance
“…During the early years of the child's life, motor and cognitive development seems to be synchronous, particularly from the six months of age 9 . Statistically significant correlation between the results of the AIMS and Bayley-II scales in children at 6 and 12 months 28 and in preterm infants of 12 and 18 months 29 have been reported, confirming our results. Recent study found a positive correlation of motor skills with cognitive skills 30 , a result similar to the present study.…”
Section: Discussionsupporting
confidence: 91%
“…During the early years of the child's life, motor and cognitive development seems to be synchronous, particularly from the six months of age 9 . Statistically significant correlation between the results of the AIMS and Bayley-II scales in children at 6 and 12 months 28 and in preterm infants of 12 and 18 months 29 have been reported, confirming our results. Recent study found a positive correlation of motor skills with cognitive skills 30 , a result similar to the present study.…”
Section: Discussionsupporting
confidence: 91%
“…In earlier studies, associations between brain volumes at term equivalent age and later outcome have been analysed up to 2 years of age, and in those studies altered volumes have been shown to relate to impaired development [4,6,13,22,28,29,34,42]. Connections between brain volumes and development have also been found later in childhood and adolescence [1,3,21,24], but volumes have then been measured simultaneously with a developmental assessment and, hence, the predictive value of smaller or larger volumes has not been considered.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of altered brain volumes on preterm children's development has been at the centre of interest in several studies. Altered volumes at term equivalent age have been shown to associate with an impaired development at 1 year [4,13], at 18 months [4], at 18-20 months [22], and at 2 years of corrected age [6,28,29,34,42]. So far, there have been no previous studies on the relationship between the brain volumes at term equivalent age and the outcome beyond 2 years corrected age.…”
Section: Introductionmentioning
confidence: 99%
“…Greater efficiency in predicting the risk of development may improve the selection of eligible infants for early therapeutic strategies 9 . Several predictive studies have been performed using neonatal and maternal risk factors to predict the outcome of development in preterm newborn infants at different ages [10][11][12][13][14] . However, these studies did not mention the use of neurobehavioural responses of premature newborn infants in the neonatal period (prior to term age) to predict global and motor outcomes prior to the end of the first year.…”
mentioning
confidence: 99%